A Giant Squamous Cell Carcinoma Arising in a Patient with Hidradenitis Suppurativa. (October 2020) - Özkur, Ezgi; Altunay, İlknur Kivanç and Celayir, Mustafa Fevzi and Çerman, Asli Aksu and Uçak, Ramazan
Abstract : ABSTRACT: Hidradenitis suppurativa (HS) is a chronic inflammatory skin disease of follicular pilosebaceous units. Chronic, active, and poorly controlled disease may lead to squamous cell carcinoma (SCC). The diagnosis and treatment of SCC in HS is particularly challenging because SCC lesions may be easily mistaken for HS lesions. Current medical literature recommends aggressive surgical excision with at least 2-cm margins. In this article, the authors describe a giant perianal SCC arising in a patient with HS who was treated with surgical resection and radiotherapy.